2009
DOI: 10.1128/jvi.01092-09
|View full text |Cite
|
Sign up to set email alerts
|

Akt Inhibitor Akt-IV Blocks Virus Replication through an Akt-Independent Mechanism

Abstract: Many viruses activate the phosphatidylinositol 3-kinase (PI3k)/Akt intracellular signaling pathway to promote viral replication. We have analyzed whether a rapidly replicating rhabdovirus, vesicular stomatitis virus (VSV), requires the PI3k/Akt signaling pathway for its replication. Through the use of chemical inhibitors of PI3k and Akt, we show that VSV replication and cytopathic effects do not require activation of these kinases. Inhibitors that block the activating phosphorylations of Akt at threonine 308 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 47 publications
6
31
1
1
Order By: Relevance
“…1B). The inability of Akt-IV to inhibit Akt phosphorylation was unexpected based on its published properties (38) but was consistent with a recent report showing that Akt-IV blocked VSV multiplication without affecting Akt phosphorylation (11). Akt-VIII has been shown to be a direct inhibitor of the kinase activity of Akt in several cell systems (2) and to have antiviral activity (1).…”
Section: Figsupporting
confidence: 60%
“…1B). The inability of Akt-IV to inhibit Akt phosphorylation was unexpected based on its published properties (38) but was consistent with a recent report showing that Akt-IV blocked VSV multiplication without affecting Akt phosphorylation (11). Akt-VIII has been shown to be a direct inhibitor of the kinase activity of Akt in several cell systems (2) and to have antiviral activity (1).…”
Section: Figsupporting
confidence: 60%
“…This finding is in agreement with previous observations that VSV replication induces the dephosphorylation of 4EB-P1 (21) and downstream effectors of Akt (42) and that VSV replication is not dependent on an active PI3k/Akt signaling pathway (24). This runs counter to what has been seen for other viruses and even other negative-strand RNA viruses, such as influenza A virus and RSV, which are known to activate Akt (26,41,60).…”
Section: Discussioncontrasting
confidence: 56%
“…We found that pharmacological inhibition of SGK1 in polarized MDCK cells resulted in disappearance of Kv7.1 channels from the surface membrane and intracellular accumulation of the channel. We observed similar effects by using Akt inhibitor IV but only at concentrations where it can also suppress SGK1 (48), suggesting that the observed effect could be due to inhibition of SGK1. In support Presented is a summary of three individual two-electrode voltage clamp experiments (n Ն 6 in each) in oocytes expressing Kv7.1 alone (normalized to 100) or in combination with Nedd4-2/Nedd4-2-CS and/or SGK/SGK KA, where Nedd4-2-CS and SGK KA are catalytically inactive versions of the respective enzymes.…”
Section: Discussionsupporting
confidence: 55%